Development of the coral index, a summary of coral reef resilience as a guide for management. (1st October 2020) - Thompson, Angus; Martin, Katherine; Logan, Murray
Abstract: Coral reef management is increasingly focused on supporting the resilience of coral communities to increasing and cumulative pressures. The coral index provides a concise summary of coral community resilience that can be efficiently communicated to a range of management and policy stakeholders. We detail the development of the index both as a technical reference for users but also as an example of an approach that could be more generally applied to the reporting of ecosystem resilience. The index is sensitive to acute impacts that are expected when coral communities are exposed to disturbances such as cyclones, bleaching events or crown-of-thorns outbreaks. Importantly, spatial and temporal trends in the index enable the identification of areas and periods of reduced resilience that suggest chronic environmental pressure imposed by runoff. The ability to summarise complex ecological processes into a single index provides an efficient and intuitive tool for the communication of where, when and which pressures are impacting ecosystem resilience. Highlights: A multi-indicator index of coral community resilience to inform management. Acute disturbances drive down coral community condition on the Great Barrier Reef. Water quality limits coral community resilience on near-shore reefs.